RITUAL POSUO ‘PINGITAN’ PADA MASYARAKAT SUKU BUTON: KAJIAN SEMIOTIKA - Adilia, Waode Fian; M. Said, Ikhwan (Universitas Hasanuddin, 2019)
This study aims to explain the stages of implementation of posuo ritual, analyze the meaning of denotation and conotation of the symbols and myths found in posuo ritual. The type of research used in this study is a qualitative description. Data collection techniques used are observation, interviews, records, and documentation. In analyzing the data it was used Roland Barthes semiotics analysis. The researchwas conducted in Wawoangi village, Sampolawa District, South of Buton regency. The results show that the stages of the implementation of the posuo ritual consist of 3, namely 1) preparation, 2) implementation which include pokunde (shampoo), pebaho (bathing), pauncura (inauguration), panimpa (blessing), padole (laid down), palego (moving limbs), pasipo (disapapi), posuo (confinement), bhaliana yimpo (change in sleeping position), matana posuo (peak of the event), and 3) closing. The symbols contained in the posuo ritual are divided into two. First, symbols in the form of implementation procedures including: pokunde, pebaho, panimpa. Seconf, symbols in the form of object/equipment including: suo (back room of the house), ndamu (ax), shroud/white cloth, and patirangga (nail dye leaves). In general, these symbols contain the meaning of purity, beauty, safety, strength, and direction of mate. Buton people believe in the posuo ritual as means to test the purity of the girls and the means to find out the direction of their soul mate. In adition, people also believe that by following the posuo ritual, a girl like bein reborn in a clean and pure state, lools more beautiful and charming, will get a good match and also a good life, especially in running on a households life.